Implementasi Pendidikan Karakter Antikorupsi Di Sekolah Dasar Se-Kecamatan Paseh Kabupaten Sumedang - Syarief, Diva Ayuvilia Putri; Kurnia, Dadang; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2019)
Abstract_This research is motivated by the implementation of anti-corruption character education that has not been written explicitly in the national curriculum, but this does not rule out the possibility that experienced teachers in elementary schools implement anti-corruption character education in hidden curiculum. The purpose of this study is to find out the implementation of anti-corruption character education in elementary school’s learning activities. This study uses a descriptive method with a cross-sectional survey. The sample used in the study is 10% of the total elementary school population. In Paseh sub-district there are 18 elementary schools, and two were selected, namely the Legok I Elementary School and Sukamulya Elementary School. This study examined teachers in the lower grade and high grades. The conclusion of this study is to apply anti-corruption character values by inserting them in learning activities with various learning methods even though not all character values have been applied.